Reliability and validity of the Indonesian version of the aging males’ symptoms (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND Aging males’ symptoms (AMS) scale was developed to study the problems of aging males, especially related to the quality of life. Currently, there is no valid and reliable Indonesian version of the AMS scale. This study was aimed to translate and evaluate the validity and reliability of the Indonesian version of the AMS scale. METHODS This cross-sectional study translated the existing AMS scale into Indonesian, which was tested in 40 years old males from May to August 2020. Cross-cultural validation of the AMS scale was conducted by translating the questionnaire from English to Indonesian by two independent-certified translators. The validity of the Indonesian version of the AMS scale was measured by conducting a Pearson correlation (r) analysis. The reliability of this questionnaire was tested and retested in 118 participants with a 2-week interval. In addition, Cronbach’s alpha value was measured and used as a reference. The first test was conducted in a corporate blood donor event in Matraman, East Jakarta, and the retest was conducted in Cipto Mangunkusumo Hospital. RESULTS The Indonesian version of the AMS scale was valid and had a good internal consistency with a Cronbach’s alpha value of 0.74. The test-retest reliability showed good reliability with an r-value of 0.981. Pearson correlation test showed that all questions in the questionnaire were valid (p<0.05) and correlated positively. CONCLUSIONS The Indonesian version of the AMS scale derived from this study is valid and has good reliability.